2011
DOI: 10.1002/jcp.22616
|View full text |Cite
|
Sign up to set email alerts
|

How dynein and microtubules rotate the nucleus

Abstract: In living cells, a fluctuating torque is exerted on the nuclear surface but the origin of the torque is unclear. In this study, we found that the nuclear rotation angle is directionally persistent on a time scale of tens of minutes, but rotationally diffusive on longer time scales. Rotation required the activity of the microtubule motor dynein. We formulated a model based on microtubules undergoing dynamic instability, with tensional forces between a stationary centrosome and the nuclear surface mediated by dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 35 publications
6
75
1
Order By: Relevance
“…There is mounting evidence that the cytoskeleton exerts forces on the nucleus to position it (20,(46)(47)(48). In this study, however, we show that as long as the cell was able to spread, inhibiting actomyosin forces, microtubulebased forces and intermediate filaments, as well as the LINC complex, did not prevent nuclear flattening.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…There is mounting evidence that the cytoskeleton exerts forces on the nucleus to position it (20,(46)(47)(48). In this study, however, we show that as long as the cell was able to spread, inhibiting actomyosin forces, microtubulebased forces and intermediate filaments, as well as the LINC complex, did not prevent nuclear flattening.…”
Section: Discussioncontrasting
confidence: 75%
“…Such forces likely originate in the cytoskeleton, which is known to link to the nuclear surface through the LINC (linker of nucleoskeleton to cytoskeleton) complex (17)(18)(19). Candidates for shaping the nucleus include microtubule motors that can shear the nuclear surface (20,21) and intermediate filaments that can passively resist nuclear shape changes by packing around the nuclear envelope or transmitting forces from actomyosin contraction to the nuclear surface (22,23). The actomyosin cytoskeleton that can push (24), pull (25,26), or shear and drag the nuclear surface (27,28) is also assumed to be a significant component of the nuclear shaping machinery in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Microtubule motors -like dynein and kinesin -generate shear forces on the nuclear surface that result in nuclear rotations in fibroblasts (Levy and Holzbaur, 2008;Wu et al, 2011), can cause nuclear translocations in epithelial cells (Wilson and Holzbaur, 2012) and are required for nuclear migration in Caenorhabditis elegans embryos Meyerzon et al, 2009). Actomyosin forces have been hypothesized to pull on the nucleus (Chancellor et al, 2010;Friedl et al, 2011;Sims et al, 1992;Wang et al, 2009;Wu et al, 2014), push on it (Friedl et al, 2011;Roth et al, 1995;Zhang et al, 2007) and shear it (Folker et al, 2011;Kim et al, 2014;Luxton et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Using similar approaches, we have also shown that dynein-microtubule interactions can bend growing microtubules and cause the nucleus to rotate. 23,24 This work shows the power of combined engineering modeling/analysis, state-ofthe art tools of molecular cell biology, and sophisticated biophysical measurements.…”
Section: ■ the Value Of Chemical Engineering "Thinking"mentioning
confidence: 99%